PEMBANGUNAN TRANSPORTASI KERETA API JALUR GOENDIH (GROBOGAN) – SOERABAJA TAHUN 1903-1922 - Panjaitan, Erik Pratama Manaor; Winarni, Retno (History Department, Faculty of Humanities, University of Jember, 2024)
This study examines the Goendih-Soerabaja railway line for the period 1903-1922. The purpose of this study is to explain the reasons for the construction of the railroad, the process of building the railroad, and its impact on the surrounding community. The results of this study indicate that the construction of the Goendih-Soerabaja railway line had a positive impact on the economy of the Dutch East Indies Government. Inaugurated on February 1, 1903, rail transportation encouraged economic growth in areas that became the path of the Goendih-Soerabaja railroad. The forced cultivation system has had a major impact on plantations, problems that have occurred due to the damage of export commodities before arriving at the port can now be resolved by the presence of rail transportation. Another factor is that the start of oil drilling operations in the Tjepu area has created the need for large-capacity oil transport in shipping to ports. Another impact of the existence of rail transportation is that the mobility of people who travel now saves more travel time. Keywords: Infrastructure; Railroad Extension; Goendih – Soerabaja Line; Capitalist Economy.